SISTEM INFORMASI BERBASIS ANDROID SEBAGAI LAYANAN TATAKELOLA BUMDES PERTANIAN PADA PEKON GEDUNG JAMBU - Fitrian, Yuri; Renaldo, Ronaldo; Joni, Joni (YHMM PUBLISHING, 2023)
The technology that develops starts from computers, laptops, so smartphones that are in accordance with the development of science. Village Owned Enterprises (BUMDes) Agriculture is one of the government agencies managed by a group of village communities in an effort to strengthen the village economy and is formed based on the results and potential of the village. BUMDes Agriculture, Pekon Gedung Jambu has several business units developed, one of which is in the field of agriculture (Agricultural Products). Every handling process of marketing activities for agricultural BUMDes production is still done manually. Based on this, it is necessary to design an online-based Information System Application (Android) as a media facility to support the performance of BUMDes management. The Andorid-Based Village-Owned Business Entity Information System (BUMDes) can provide an overview of the functions of Android-based applications which will later make it easier for BUMDes to manage management data and deliver agricultural product information. The process stages of the system created using Data Flow Diagrams (DFD), waterfall system development methods, PHP and MySQL programming languages. This system was built to assist in presenting information about BUMDes based on Android, and assisting the community in obtaining information on BUMDes in Pekon Gedung Jambu, as well as making it easier for administrators to view or process the latest BUMDes data.